Integrating Artificial Intelligence into Strategic Leadership: Implications for Ethical Governance, Employee Trust, and Organizational Performance in Indonesia - Safina, Wan Dian; Hutasuhut, Julianto; Pratama, Nugraha; Mulyono, Hardi; Rahmat, Muhammad (Ilomata International Journal of Management, 2026)
Artificial intelligence (AI) is transforming strategic leadership, yet existing research in Indonesia has not systematically integrated how AI-enabled leadership, ethical governance, and employee trust are jointly represented across national policy, academic, and practitioner discourse. This study addresses this gap through a qualitative document analysis of a purposively assembled corpus of 42 Indonesian documents (2019–2025), including national policies (n=5), sectoral guidelines (n=4), academic articles (n=18), practitioner reports (n=10), and legal commentaries (n=5). Documents were retrieved via Google Scholar, institutional websites (Kominfo, OJK), and consultancy repositories using keywords: "AI leadership Indonesia", "etika kecerdasan buatan", "tata kelola AI", "kepercayaan karyawan AI", and "AI governance Indonesia". Inclusion criteria required direct relevance to AI in leadership/governance/workplace contexts, Indonesian focus, and publication between 2019-2025. Analysis treated documents as social artefacts, coding at the paragraph level using an iterative codebook (initial codes: n=24; final themes: n=4). Themes were validated through cross-source triangulation (requiring support from ≥2 document types) and peer debriefing (n=2 independent reviewers). Documentary evidence indicates that AI is framed as augmenting strategic sensing and performance monitoring, while generating concerns about data protection and algorithmic bias. National ethics circulars and sectoral guidelines begin to structure AI governance but are described as principle-heavy and unevenly translated into practice. Employee trust is portrayed as contingent on transparency, fairness, human oversight, and voice. Building exclusively on this documentary synthesis (not primary organizational field data), the article proposes a novel Indonesia-specific integrated framework in which ethical AI governance mechanisms mediate the relationship between AI-enabled strategic leadership and trust-based organizational performance. The framework’s novelty lies in specifying governance mechanisms (policies, assessments, committees, transparency, training) as mediators rather than moderators, grounded in an emerging-market context with high power distance and partial regulation.